Peran manajemen risiko dalam pencegahan dan penanganan kredit macet pada perbankan - akbar, moh rafi (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of risk management in preventing and handling non-performing loans in the banking sector. The method used is a literature study by reviewing various relevant sources. The results show that risk management plays an important role in the stages of prevention, early detection, control, and evaluation. In the prevention stage, banks apply the 5C principles to assess customer feasibility. Furthermore, an early warning system is used to detect potential problem loans. In the control stage, banks implement credit restructuring and establish loan loss provisions (CKPN). Evaluation is carried out periodically to improve credit policies. Effective risk management can minimize non-performing loans, maintain financial stability, and enhance public trust in banks.